Deciphering the ABA and GA biosynthesis approach of Bacillus pumilus, mechanistic approach, explaining the role of metabolic region as an aid in improving the stress tolerance - Shifa Shaffique; Anis Ali Shah; Peter Odongkara; Hosam O. Elansary; Abdul Latif Khan; Arjun Adhikari; Sang-Mo Kang; In-Jung Lee (Scientific Reports)
Abstract Bacillus pumilus plays an essential role in agricultural applications as a beneficial microbe and for sustainable agriculture production. However, the underlying mechanisms of B. pumilus strains remain unclear as to how they are beneficial for plants as stress tolerant and growth promoters. Bacillus pumilus was isolated from the rhizosphere soil of Artemisia vulgaris. NGS (next-generation sequencing) was performed for the strain to gain new insights into the molecular mechanisms underlying plant-microbial interactions. NGS revealed 3,910 genes, 3294 genes with protein-coding, and 11 functional genomic regions related to diverse agronomic traits including stress tolerance. We identified the two possible phytohormone biosynthesis approaches from metabolic regions1(terpense→diterpense→betacarotene→xanthoxin→ABA)2(terpense→diterpense→geranyl diphosphate →C20 →GA). Several gene clusters related to the biosynthesis of phytohormones, stress tolerance, and agricultural diversification were predicted. The genome provides insights into the possible mechanisms of this bacterium for stress tolerance and its future applications. The genomic organization of B. pumilus revealed several hallmarks of its plant growth promotion and pathogen suppression activities. Our results provide detailed genomic information for the strain and reveal its potential stress tolerance mechanisms, laying the foundation for developing effective stress tolerance strategies against abiotic stress.